Experience of Pseudospark Switch Operation in Pulse Power Applications; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Voitenko N. V. Nikita Valerievich; Yudin A. S. Artem Sergeevich; Kuznetsova N. S. Nataliya Sergeevna; Bochkov V. D. (2015, 2015)
Title screen